Development of a KPI Subsystem for a Russian Confectionery Company: A Case Study - Vaskova, Nadezhda; Kirushin, Sergey; Malafeev, Alexey (International Journal of Industrial Engineering and Management, 2017)
The article presents a case study of KPI subsystem development based on the application of methods and tools of lean production in a Russian confectionery factory. We report on an analysis of production problems at the enterprise, as well as proposed solutions and results of their implementation. The lean KPI subsystem resulted in significant improvements in the company. The results of this case study are relevant for business practices in general, as the proposed measures can be used to improve a company’s investment attractiveness. Additionally, the findings are useful for lean managers working in the confectionery industry, as our study illustrates key success factors, as well as the impact androle of lean manufacturing in this industry. Article history: Received (17.01.2017); Revised (12.04.2017); Accepted (07.05.2017)